Environmental drivers of habitat use by common bottlenose dolphins (Tursiops truncatus) in the Indian River Lagoon, Florida, USA. Issue 2 (21st November 2020) - Greller, Rachael; Mazzoli, Marilyn; Titcomb, Elizabeth; Nelson, Brandy; Paperno, Richard; Markwith, Scott H.
Abstract: Anthropogenic impacts in estuarine systems can influence marine mammal habitat use, population dynamics, fitness, and mortality events. The objective was to examine habitat use among the resident common bottlenose dolphin ( Tursiops truncatus ) population inhabiting the Indian River Lagoon, Florida, and the influences of variation in environmental factors and prey availability in 2003–2015. We utilized photo‐identification surveys, stratified random samples of prey, and environmental variables collected monthly. Kernel density estimation was used to determine the magnitude‐per‐unit area of dolphins across the IRL by wet and dry seasons each year, the values were used as a response variable in classification and regression tree analyses with fish community and environmental variables as predictors. Spatial patterns in dolphin density in the IRL were associated with salinity and dissolved oxygen levels, which are in part associated with freshwater discharges of nutrient and algae laden waters from the region's storm water management system. These findings isolate locations of concern for management of dolphin habitat, and anthropogenic drivers of dolphin distributions requiring further research.